Normanowie w dziełach Geralda z Walii a świat bizantyński - Böhm, Marcin (Vox Patrum, 2018)
The main purpose of this paper is to analyze the selected works of one of the twelfth century Norman historian living in the British Isles, Gerald de Barri of Wales (1146-1223) in terms of his knowledge of the Byzantine world and its correlation with the Normans (from England and Southern Italy). The term Byzantine world has been evolving for several decades. Today it refers no longer just to the land of the former East European Empire, which later transformed itself into the Greek Byzantium, but it can be referred to the Balkans or the Kingdom of Normandy, while scientists are constantly expanding its borders with the help of other sciences such as archeology. We will do this based on his work: De instructione principis, Topographia Hibernica, Expugnatio Hibernica, Itinerarium Cambriae and Descriptio Cambriae. Selected by Gerald of Wales the themes of the Byzantine and Norman kingdoms of Sicily, which appear in his five works cited above, are proof of the broad political horizons of the elites from British Isles that were associated with the Plantagenet dynasty. Gerald was never in Sicily, in Byzantium or in the Holy Land, but he had some source in sight, both in the form of eyewitness accounts of events and in the accounts of contemporary writers, which does not diminish the credibility of the data he cites. Better and more strongly, he was interested in the facts of the kingdom of Normans in Sicily than in Byzantium. Such a state of affairs seems to be understandable, as he saw in them both a political partner and, to some extent, a model to imitate, especially in the aspect of conducting politics against the conquered peoples.